Ulam Panjo: Program Peningkatan Kesehatan Mental Siswa untuk mewujudkan Kesiapan Belajar - Nugroho Wibowo (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Mental health significantly influences learning readiness. Good mental health is the foundation for students to manage stress, absorb material, and build self-confidence to achieve learning goals. One in three Indonesian teenagers experiences mental health problems, the two most common mental disorders being anxiety disorders and depression. This article aims to provide an overview of student mental health management through the Ulam Panjo program (Student Service Unit for Mental Health Improvement). This study uses a qualitative descriptive approach supported by a literature review, through the stages of planning, implementation, observation, and reflection. The study was conducted at SMK Negeri 1 Girisubo. The results of the implementation of the Ulam Panjo program have a positive impact on students experiencing mental health disorders. It was concluded that the implementation stages of the Ulam Panjo program consist of three stages: data collection, analysis, and maintaining students' mental health conditions. Supporting factors in this program are the active participation of the Community Health Center (Puskesmas) and Koramil (Military Command) in implementing activities carried out by the school, while inhibiting factors are the lack of openness of parents of students with mental health problems and not all students with mental health disorders feel open and willing to communicate with the guidance and counseling teacher.